\(-5x^2+16x-3=0\)
\(-5x^2+x+15x-3=0\)
\(x\cdot\left(-5x+1\right)-3\cdot\left(-5x-1\right)=0\)
\(\left(-5x-1\right)\cdot\left(x-3\right)=0\)
\(\hept{\begin{cases}-5x-1=0\\x-3=0\end{cases}\Rightarrow\hept{\begin{cases}x=-\frac{1}{5}\\x=3\end{cases}}}\)
Vậy.......
-5x^2 +15x +x-3=0
5x(-x +3)-(-x+3)=
(5x-1)(-x+3)=0
5x-1 =0 hoặc -x+3=0
x=1/5 hoặc x=3
tự ghi lại đề
-5x^2+15x+x-3=0
(-5x^2+15x)+(x-3)=0
-5x(x-3)+(x-3)=0
(-5x+1)(x-3)=0
-5x-1=0 -5x=1 x=-1/5
x-3=0 x=3 x=3
\(-5x^2+16x-3=0\)
\(-5x^2+x+15x-3=0\)
\(x\left(-5x+1\right)+3\left(5x-1\right)=0\)
\(x\left(1-5x\right)-3\left(1-5x\right)=0\)
\(\left(1-5x\right)\left(x-3\right)=0\)
\(\Rightarrow\orbr{\begin{cases}1-5x=0\\x-3=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{5}\\x=3\end{cases}}}\)